Substituted metal carbonyls. XXII . Synthesis of 1,1′-bis(diphenylphosphino)ferrocene-bridged complexes with two heterometallic AuM (M Mn and Re) bonds - Low, P.M.N. (2014)
Journal of Organometallic Chemistry